2020
DOI: 10.1007/s10570-020-03583-y
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the influence of key parameters on the stabilisation of cellulose-lignin composite fibres

Abstract: The high cost of carbon fibre continues to limit its use in industries like automotive, construction and energy. Since the cost is closely linked to the precursor, considerable research has focussed on the use of low-cost alternatives. A promising candidate is a composite fibre consisting of blended cellulose and lignin, which has the added benefit of being derived from sustainable resources. The benefits of blending cellulose and lignin reduce some of the negative aspects of converting single component cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…To maximize the yield, a stabilization profile with a lower temperature and a longer residence time may be the best, since a temperature closer to the degradation temperature of the raw materials shortens the stabilization time but usually at the expense of the yield. 21 , 37 …”
Section: Resultsmentioning
confidence: 99%
“…To maximize the yield, a stabilization profile with a lower temperature and a longer residence time may be the best, since a temperature closer to the degradation temperature of the raw materials shortens the stabilization time but usually at the expense of the yield. 21 , 37 …”
Section: Resultsmentioning
confidence: 99%
“…The FTIR spectrum contains mostly H 2 O (at 1250–1500 and 3500–4000 cm –1 ) and CO 2 (at 2300–2400 cm –1 ). , A small peak at 1160 cm –1 accounts for C–O–C bonds, while another small band around 2700–3000 cm –1 accounts for C–H bonds. , Both peaks suggest the existence of trace amounts of cellulose or lignin monomers. , With negligible other pyrolysis products observed, other than H 2 O and CO 2 , it can be proposed that stabilization was conducted at a temperature that avoided severe pyrolysis and a reduction in char yield. Importantly, this temperature, which is typically chosen from the onset of degradation from the TGA curve, is still able to achieve a comparatively high stabilization rate …”
Section: Resultsmentioning
confidence: 99%
“…The increase in char yield is also higher for lignin compared to cellulose, further indicating the dependency of lignin stabilization on oxygen. Unlike cellulose, lignin is a complex mixture of polyphenolic polymers containing three basic aromatic monomer units as shown in Figure . , Therefore, because of the more thermally stable aromatic structure, oxygen is needed to transform these aromatic rings to aldehydes, ketones, quinones, or acids which can form a cross-linked network during stabilization. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of processing parameters (i.e., draw ratio, stabilization/carbonization temperature, lignin content, etc.) on the structure and mechanical properties of lignin/cellulose precursor fibers and carbon fibers have been investigated systematically [ 139 , 155 , 156 , 157 ], from which it is concluded that the cellulose constituent dominates precursor fiber structure and mechanical performance. Increasing lignin content decreases fiber strength due to the disturbance of oriented cellulose crystallites [ 141 , 158 , 159 ] and increases carbon yield [ 160 ] due to lignin’s carbon-rich structure.…”
Section: Mechanical Performance Of Lignin-based Fibersmentioning
confidence: 99%